2023
DOI: 10.3390/v15091838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mixed Baculovirus Infections in Biological Control: A Comprehensive Historical and Technical Analysis

María Leticia Ferrelli,
Ricardo Salvador

Abstract: Baculoviruses are insect-specific DNA viruses that have been exploited as bioinsecticides for the control of agricultural and forest pests around the world. Mixed infections with two different baculoviruses have been found in nature, infecting the same host. They have been studied to understand the biology of virus interactions, their effects on susceptible insects, and their insecticidal implications. In this work, we summarize and analyze the in vivo baculovirus co-infections reported in the literature, main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Studies from Kopanke et al observed a similar trend in C. sonorensis housed at 20 °C that were exposed via blood meal to BTV-2 and BTV-10, even though this colony demonstrated poor competency for BTV-2 [ 25 ]. Virus coinfection studies (specifically Baculoviruses) indicate three different possible outcomes of virus coinfection in the insect vector: synergism (increased mortality), neutralism, and antagonism (decreased mortality) [ 39 , 40 ]. It would be constructive to further investigate if BTV coinfections could overwhelm insect immune defenses and result in decreased lifespans.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Kopanke et al observed a similar trend in C. sonorensis housed at 20 °C that were exposed via blood meal to BTV-2 and BTV-10, even though this colony demonstrated poor competency for BTV-2 [ 25 ]. Virus coinfection studies (specifically Baculoviruses) indicate three different possible outcomes of virus coinfection in the insect vector: synergism (increased mortality), neutralism, and antagonism (decreased mortality) [ 39 , 40 ]. It would be constructive to further investigate if BTV coinfections could overwhelm insect immune defenses and result in decreased lifespans.…”
Section: Discussionmentioning
confidence: 99%
“…All the above-mentioned limiting factors on the success of baculoviral bioinsecticide led to investigations of enhanced effectiveness through its combination with biorationals or synthetic low-toxicity insecticides on a range of noctuid pests [30][31][32][33]. A dual-action bioinsecticide was also explored using mixed entomopathogens [34][35][36][37], but this was not always conclusive [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…This is not unusual with SfMNPV; younger larvae are most susceptible to the virus, while older ones develop resistance [4]. However, there are some data showing that older host instars may be suitable for studying synergism between two mixed baculoviruses [34]. From another perspective, the extent to which the discovered SfMNPV-KA1 can kill close genera/family counterparts is a researchable question.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, our knowledge of the prevalence and biodiversity of insect-specific viruses in insect populations is very limited; this is particularly the case for those viruses that infect agricultural pests. To date, most research on viruses for insect pest control has focused on baculoviruses (arthropod-specific DNA viruses) [ 6 , 7 ] and the benefits offered by other viruses in this context has received little attention or recognition. When deployed as biological control agents, insect-specific RNA viruses are capable of causing significant reductions in the field populations of agricultural and forestry pests [ 8 ] and aerial applications of tetraviruses and picorna-like viruses have been especially successful against leaf-eating caterpillar pests in oil palm and coconut tree plantations [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%